2016
DOI: 10.1111/clr.12985
|View full text |Cite
|
Sign up to set email alerts
|

Vertical augmentation of the posterior atrophic mandible by interpositional grafts in a split‐mouth design: a human tomography evaluation pilot study

Abstract: The GEISTLICH BIO-OSS and STRAUMANN BONECERAMIC interposition grafts exhibited similar and sufficient dimensional stability and volume gain for short implants in the atrophic posterior mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This suggested that the graft was stable just after implant placement. Xenogenic grafts are able to integrate into the host bone, in sandwich cases promoted by two sides of vascularized recipient bone (Cordaro & Terheyden, ; Domingues et al, ; Laino et al, ; Mounir, Mounir, Abou‐Elfetouh, & Shaker, ). Bovine bone integrates with regenerated bone but is resorbed slowly (Bechara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the graft was stable just after implant placement. Xenogenic grafts are able to integrate into the host bone, in sandwich cases promoted by two sides of vascularized recipient bone (Cordaro & Terheyden, ; Domingues et al, ; Laino et al, ; Mounir, Mounir, Abou‐Elfetouh, & Shaker, ). Bovine bone integrates with regenerated bone but is resorbed slowly (Bechara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the surface roughness of the structure, the higher the rate at which the ions are released. Fernandes et al noted that, among these ions, Ag + is the common ion that is doped on glass and glass-ceramics studied in recent studies [ 339 ]. Hence, these materials play a crucial role at the site of dental implants as Escherichia coli, Staphylococcus aureus , S. epidermidis , and Pseudomonas aeruginosa are identified to be present in 90% of all dental implants [ 339 , 340 , 341 , 342 ].…”
Section: Biomimetics Of Periodontal Tissue Engineering and Regenermentioning
confidence: 99%
“…Fernandes et al noted that, among these ions, Ag + is the common ion that is doped on glass and glass-ceramics studied in recent studies [ 339 ]. Hence, these materials play a crucial role at the site of dental implants as Escherichia coli, Staphylococcus aureus , S. epidermidis , and Pseudomonas aeruginosa are identified to be present in 90% of all dental implants [ 339 , 340 , 341 , 342 ]. It has been demonstrated that 45S5 Bioglass, which contains hydroxycarbonate apatite on its surface, can suppress S. sanguis , S. mutans , and Actinomyces viscosus [ 318 , 339 ].…”
Section: Biomimetics Of Periodontal Tissue Engineering and Regenermentioning
confidence: 99%
See 2 more Smart Citations